Respuesta :

Answer:1) 3=(x+2)^2.
2)A)x=-2 squareroot of 3

Step-by-step explanation:

khan

We can rewrite the equation as ( x + 2 )² = 3

The value of x is -2 ± √3

What is a quadratic equation?

'A quadratic equation is an algebraic equation of the second degree in x. The quadratic equation in its standard form is ax² + bx + c = 0, where a and b are the coefficients, x is the variable, and c is the constant term.'

According to the given problem,

Given equation: x² + 4x + 1 = 0

The equation can be converted to a perfect square by adding 3 on both sides,

⇒ x² + 4x + 1 + 3 = 0 + 3

⇒ x² + 4x + 4 = 3

⇒ ( x + 2 )² = 3

Here, c = 2

         d = 3

Now,

Since, this number cannot be factorized,

We apply,

-[tex]\frac{b(+-)\sqrt{b^{2}-4ac } }{2a}[/tex] where, a, b, c are the coefficients of x², x,

= [tex]\frac{-4(+-)\sqrt{4^{2}-4 } }{2}[/tex]

= [tex]\frac{-4(+-)\sqrt{12} }{2}[/tex]

= [tex]-2(+-)\sqrt{3}[/tex]

Hence, we can conclude the value of the equation to be -2 ± √3.

Learn more about quadratic equations here: https://brainly.com/question/2263981

#SPJ2

ACCESS MORE